Tinjauan Yuridis Terhadap Pelanggaran HAM Dalam Human Trafficking Dari Perspektif Hukum Internasional - Edghar Abdullah Albab; Ahmad Izzul Ramadhani; Eka Sari Nurliana; Reniarti Asma Inayah; Rizkya Fitri Ananda Hariyanto (Westscience Press, 2022)
Basically the fulfillment of Human Rights is the obligation of the State towards its citizens. The state itself can be interpreted as a legal subject that has a role and responsibility for the consequences of human rights violations. This is included in the framework of maintaining the safety and security of every citizen. So the state's firmness is needed in eradicating actions that harm and threaten the safety of the basic rights of citizens. This study aims to determine the arrangements regarding the crime of human trafficking in international instruments and legal protection for trafficking victims, both in international law and Indonesian national law. Secondary data, namely data obtained from reading materials and libraries is the type of data material used in this study. This research also includes a type of descriptive normative research. The results show that arrangements regarding the prohibition of human trafficking according to international law are regulated in the 2000 Palermo Protocol, specifically in Protocol II and implemented by Indonesia with Law no. 21 of 2007. Human trafficking is still rife and increasing, this practice is a universal violation of human rights to live free from all forms of slavery. The standards for protecting and fulfilling the rights of victims themselves are also regulated in the Palermo Protocol. This research is related to the difference between theory and the fact that even though there have been many regulations regarding the prohibition of human trafficking, there are still many acts of human trafficking in this world. Thus, this research can be used as a reference by the academic community, especially in the field of law and law enforcement officials. In addition, it can also be used as a reference to study how the legal responsibility of traffickers is in the perspective of international law.